Problem Based Learning: cultural diverse students' engagement, learning and contextualized problem solving in a mathematics classroom - P.n Chakrabarty, Sheila Chakrabarty; Mohamed, Noor Shafini (Koperasi Kolej Universiti Islam Antarabangsa Selangor Berhad (KOKISDAR), 2013)
In today’s fast changing world students has to be equipped with knowledge and also skills. The current teacher-student centered settings are unable to produce students who will be adaptive in the workplace. Obtaining a good grade in Mathematics for foundation students who will be undertaking Engineering, Medicine, Pharmacy, Information Technology and Architecture is crucial as this will ensure a place in degree level. Therefore the extent in which teachers deliver their materials is important to make sure that students understand and be able to apply the knowledge learned in their daily lives. These students come from various countries mainly from Bangladesh, China, Yemen, Thailand, Saudi Arabia, Jordan and Syria. This paper presents the findings where Problem Based Learning approach was adopted to teach mathematics to students who come from diverse cultures. PBL is a collaborative method where it was found from the study conducted that it is a good approach to bring students from diverse cultures together toward a common goal. Students were observed and interviewed in the second semester of their foundation course. PBL activities were conducted in stages and since in PBL, students direct their own learning and work in a group, hence they become motivated, self-confident, and proactive. At the initial stage, there were segregation, meaning that students from the same countries preferred to be grouped together, but as they became familiar with the PBL approach they became more comfortable working with students from different countries. The findings showed that some students have influence on other students in terms of how much and what they learned. It was evident that PBL has positive implications on how student learned, generating ideas to arranging these ideas in a meaningful manner. By doing that, students managed to cultivate skills like problem solving, critical thinking and communication skills. It also helped students to see connections between mathematics and its application in the real world. This encourages lifelong learning and unity amongst students.